Assessment of RES impact on faults analysis in a weak interconnected power system - Karapidakis Emmanuel; Mozakis Ioannis (E3S Web of Conferences)
Fault analysis in power grids is a critical factor in ensuring the stability and reliability of power systems. Various approaches have been developed to address the complexity of fault detection, diagnosis and analysis. These methods range from traditional manual techniques to advanced artificial intelligence (AI) and machine learning models. In addition, approaches include simulation methods, analytical techniques and stochastic computation, which aim to understand the impact of different conditions on network performance. In this paper, PowerWorld software is used, which plays an important role in power grid fault simulation and analysis, providing valuable information for grid management and protection. In this study, the power world software has been used as a method of calculation and simulation of fault analysis in an interconnected electricity grid, where the effect of integration of RES is studied and three different penetration scenarios are considered.